Precariousness, Diabetes Control and Complications in French Guiana - Linière, Samuel; Nacher, Mathieu; Drak Alsibai, Kinan; Mergeayfabre, Mayka; Hafsi, Nezha; Charpin, Aurelie; Misslin-Tritsch, Caroline; Carod, Jean-François; Aurelus, Jean Markens; De Toffol, Bertrand; Ntoutoum, André; Kakamba, John Bukasa; et al. (Frontiers in Endocrinology, 2022)
Aims The social parameters of an individual impact the incidence of cardiovascular diseases. French Guiana, an overseas French territory with a lower standard of living than France, has a prevalence of diabetes mellitus that is twice that of mainland France. In this context we aimed to study the relation between precariousness, diabetes complications and glycemic control. Methods A multicenter prospective cohort was initiated since May 2019. 1243 patients were included and their outcomes and history were compared between the precarious and non-precarious based on their EPICES score, a score that measures social isolation and precariousness. Results 73.3% of the sample was considered precarious. Retinopathy was significantly more frequent among the deprived. There were no significant differences for other macro or microvascular complications.There was a significant difference in Glycated Haemoglobin between the precarious and non-precarious groups (8.3% (67 mmol/l) vs 8.8% (73mmol/l)). After adjusting for potential confounders, precariousness was no longer associated with poor glycemic control; the independent factors significantly associated with poor glycemic control were: not being fluent in French, having creole or portugese as mother language, and not having any insurance. Conclusions Precariousness is a risk factor for retinal complications in patients with diabetes mellitus in French Guiana. In this chronic disease, the universal healthcare system alleviates health inequalities for many, but not all, diabetic complications.Translation and cultural mediation may further reduce health inequalities in this multicultural territory where a substantial proportion of the population is not fluent in French.